RETRACTED: Mechanical and biocompatible properties of the poly(lactide-co-glycolide) matrices produced by antisolvent 3D printing - Mokrousova Victoria; Nedorubova Irina; Vasilyev Andrey; Kuznetsova Valeriya; Mironov Anton; Khvorostina Maria; Bukharova Tatyana; Popov Vladimir; Goldshtein Dmitry; Losev Fedor; Kulakov Anatoly (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001